2001
DOI: 10.1021/ma011117q
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic and Mechanical Properties of Epoxy/Multifunctional Polyhedral Oligomeric Silsesquioxane Nanocomposites and Epoxy/Ladderlike Polyphenylsilsesquioxane Blends

Abstract: Aliphatic epoxy composites with multifunctional polyhedral oligomeric silsesquioxane (POSS) ((C 6H5CHCHO)4(Si8O12)(CHdCHC6H5)4) nanophases (epoxy/POSS 95/5 and 75/25) and epoxy blends with the prepolymer of ladderlike polyphenylsilsesquioxane (PPSQ) (95/5, 90/10, and 85/15) were prepared by solution casting and then curing. These composites and blends were studied by dynamic mechanical thermal analysis (DMTA) and mechanical testing. The POSS units incorporated into the epoxy network are well dispersed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
187
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 275 publications
(198 citation statements)
references
References 11 publications
7
187
0
Order By: Relevance
“…The epoxy/POSS nanocomposite with 10% POSS was further postcured at T g þ 10 C (190 C) for 36 h to reach full conversion; a longer cure time and/or higher cure temperature has also been found in other work 30 to be required for the nanocomposites to reach the same degree of crosslinking as the neat system. The samples were cured in their glass tubes under air atmosphere, but the top few centimeters of sample (that was potentially exposed to air) were not used.…”
Section: Curing Of Epoxy/poss Nanocompositesmentioning
confidence: 97%
See 2 more Smart Citations
“…The epoxy/POSS nanocomposite with 10% POSS was further postcured at T g þ 10 C (190 C) for 36 h to reach full conversion; a longer cure time and/or higher cure temperature has also been found in other work 30 to be required for the nanocomposites to reach the same degree of crosslinking as the neat system. The samples were cured in their glass tubes under air atmosphere, but the top few centimeters of sample (that was potentially exposed to air) were not used.…”
Section: Curing Of Epoxy/poss Nanocompositesmentioning
confidence: 97%
“…37 The moduli of the POSS-filled nanocomposites similarly depend on the POSS structures. The glassy modulus of the nanocomposites is found to either increase due to the nanoreinforcement of the nanoparticles 27,31,39 or decrease; 37 furthermore, the rubbery modulus also either increases presumably due to the increased crosslink density or the reinforcement of the nanoparticles 28,30,43 or decreases due to the decreased crosslink density associated with the flexible structure of the POSS. 27 One study also showed that the instantaneous modulus of the nanocomposites is not affected by the incorporation of POSS, although the physical aging process of the composites in the glassy state was found to be retarded.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…To overcome these drawbacks, many types of polymer-filler composites have been developed, in which the epoxy resins are reinforced with modifying agents, such as fillers, polyhedral oligosilsesquioxanes, dendrimers etc. [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In these materials the cubes can be connected to one another by organic components with known architecture and lengths of the order of 3-5 nm, forming composites with completely defined interfacial component between organic and inorganic phase [19][20][21][22][23][24]. Nanocomposite materials can offer novel properties, such as significant improvements in tensile modulus, fracture toughness, thermal and oxidation resistance, and reduced flammability that can only be explained by extensive organic-inorganic interfacial interactions [10][11][12][13][14][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%